Competitor Threats and the Competitive Advantage among Commercial Banks in Kenya - Waithaka, Paul (European Scientific Journal, ESJ, 2020)
Globalization and technological advancement have in a big way altered the business landscape, making it difficult for banks to sustain competitive advantage. The need to enhance competitiveness has forced firms to consider competitive intelligence not only as a tool to guard against competitor threats but also as a mechanism for discovering new opportunities and trends. Competitive intelligence contributes to continuous improvement of the quality of products, services and solutions offered by companies to their clients as well as increasing a firm’s innovative capability. Competitor threats have been identified as one of the competitive intelligence domains that a firm needs to focus on in order to gain and sustain competitive advantage. This paper sought to examine the effect of competitor threats on the competitive advantage among commercial banks in Kenya. The target population for the study were directors or managers in-charge of planning or strategy in each of the forty banks in the country. Primary data was collected using a semi structured questionnaire. The questionnaire was tested for both validity and reliability and was found to have met the required threshold. A response rate of 77.5% was achieved in the study and this was adequate for analysis. The study found that competitor threats had significant effect on the ability of banks to sustain competitive advantage. The study therefore concluded that competitors’ threats are real and could inhibit a company’s strategy from succeeding in the marketplace and therefore should be detected early. The study therefore recommends that banks should increase the resources devoted to monitoring the competitive landscape to enable early identification of competitors’ threats. The study further recommendsthat banks should develop strategies to neutralize, eliminate or ameliorate those threats.